2020
DOI: 10.1172/jci.insight.133811
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of an immune infiltration signature in diffuse lower-grade gliomas

Abstract: BACKGROUND. Lower-grade gliomas (LGGs) vary widely in terms of the patient's overall survival (OS). There is no current, valid method that could exactly predict the survival. The effects of intratumoral immune infiltration on clinical outcome have been widely reported. Thus, we aim to develop an immune infiltration signature to predict the survival of LGG patients. METHODS. We analyzed 1216 LGGs from 5 public data sets, including 2 RNA sequencing data sets and 3 microarray data sets. Least absolute shrinkage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Furthermore, we further analyzed the relationship between hematological indicators and IDH mutation subgroups, and found that only FIB had a signi cant difference between G4 IDH-wt and G3 IDH-mut or G4 IDH-mut. Previous study had shown that the immune response of the tumor microenvironment was more susceptible to the modulation of IDH mutation status in lower-grade gliomas 15 . This result suggested that there may be a connection between systemic and local in ammation and coagulation and immune regulation.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, we further analyzed the relationship between hematological indicators and IDH mutation subgroups, and found that only FIB had a signi cant difference between G4 IDH-wt and G3 IDH-mut or G4 IDH-mut. Previous study had shown that the immune response of the tumor microenvironment was more susceptible to the modulation of IDH mutation status in lower-grade gliomas 15 . This result suggested that there may be a connection between systemic and local in ammation and coagulation and immune regulation.…”
Section: Discussionmentioning
confidence: 95%
“…To date, some existing models have used IRGs as a prognostic predictor of glioma patients (33,34). A study examining the gene expression pattern of tumor immune infiltration identified an association with LGG malignancy, and a risk model based on 20 IRGs with different expression levels was shown to present decent OS prediction abilities for LGG (13). However, many prognosis-related models are limited by factors such as small sample size and the lack of sufficient validation.…”
Section: Discussionmentioning
confidence: 99%
“…IRGs have also been regarded as biomarkers to predict prognosis of cancer patients (12). A recent study constructed a stable IRG signature that was found to serve as an effective and predictive prognostic model among primary LGG patients (13).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor grade was a good predictor of survival, and both previous and the present found the association between WHO grade II gliomas and better OS . Different immune in ltration types may contribute to the difference in prognosis between Oligodendroglioma and astrocytoma (Song and Weng et al, 2020). Pleomorphic xanthoastrocytoma (PXA) is a rare brain tumor mainly affecting pediatric and young adults (Vaubel and Zschernack et al, 2020).…”
Section: Discussionmentioning
confidence: 99%